A study of binder formulation in metal injection moulding - Foong, Mun Leong. (2009)
This project seeks to understand the underlying fundamentals in the formulation of a binder system and feedstock to optimise the MIM process. Study was made on a EVA-beeswax binder and carbonyl iron powder feedstock system. Throughout the entire work, the focus was on studying the physical binder-powder interactions. The properties investigated include rheology, thermal and mechanical properties.